Evolutionary mechanism of YBO3 whisker and its effect on the properties of YIG ferrite joint brazed by Bi2O3–B2O3–SiO2–ZnO glass. Issue 1 (1st January 2021) - Xu, Jiujie; Lin, Panpan; Chen, Qianqian; Zhao, Xuan; He, Peng; Lin, Tiesong; Jiang, Chonglai; Liu, Yan; Liu, Hongzhi; Long, Weimin
Abstract: The Bi2 O3 –B2 O3 –SiO2 –ZnO glass braze was used to bond the Yttrium iron garnet (YIG) ferrite. The (i) microstructure evolution and (ii) mechanical and dielectric properties of YIG/YIG joints were investigated. The results show that the bonding of YIG ferrite with Bi2 O3 –B2 O3 –SiO2 –ZnO glass braze was effective at brazing temperature. There were nearly free of defects. At the YIG/glass interface, gray YBO3 whiskers, gray layered YBO3, and black block Fe2 O3 phases were observed due to the reaction of the glass braze and YIG ferrite. As the brazing temperature or holding time increased, the gray layered YBO3 phase turned into YBO3 whisker gradually. This is because the B–O bonds of [B3 O9 ] ring in the unit cell of the layered YBO3 are broken and evaluated to [BO4 ] in the cell of YBO3 whisker. The shear strength reached a maximum of 65 MPa for the joint brazed at 725 °C because of the enhancement effect of YBO3 whisker and Fe2 O3 phases. The relative dielectric constant of the joint brazed at 700 °C was about 16, which was close to that of YIG ferrite. Moreover, the dielectric loss of this joint was about 0.005.